Application of TCM network pharmacology and experimental verification to explore the mechanism of kaempferol against epilepsy - Jiaojiao Zhao; Xia Qin; Lei Yang; Han Guo; Siruan Chen; Keying Tian; Qinghui Guo; Wenya Zhao; Panpan Zhang; Zhanfeng Jia; Zuxiao Yang; Dezhi Kong; et al. (Brain Research Bulletin)
Background: Kaempferol (KF), the main active ingredient in identifying the authenticity of safflower, has a variety of pharmacological activities and neuroprotective effects. However, the mechanism of KF in the treatment of epilepsy remains unclear. This study aimed to investigate the protective effects of KF on epilepsy and its related mechanisms. Methods: Network pharmacology was used to explore the targets and mechanisms of safflower antiepileptic action. The protective effect of KF on epilepsy was assessed in the behavior and tissues of epileptic mice. Additionally, the impact of KF on the excitability and calcium transients of rat cortical neurons and α-amino-3-hydroxy-5-methyl-4-isoxazole-propionicacid receptor (AMPAR) were investigated using patch clamp and calcium imaging techniques. Results: Network pharmacology indicated safflower could be involved in calcium signaling pathways and calcium channel inhibitor activity. Experimental validation demonstrated that KF delayed seizure onset and mitigated neuronal damage in the prefrontal cortex of mice. It also reduced neuronal excitability, as indicated by action potential parameters, and suppressed Glutamate (Glu)-induced calcium transients. In tsA201 cells, KF inhibited AMPAR-mediated currents, suggesting a role in regulating [Ca2+]i homeostasis. Conclusion: These results indicate that KF's anticonvulsant properties may arise from its neuroprotection against cell injury, edema, and necrosis, its reduction of neuronal hyperexcitability, and its prevention of calcium-induced cytotoxicity, potentially involving AMPAR modulation. This study positions KF as a promising candidate for epilepsy therapy, offering a scientific foundation for its clinical investigation.